Regulation of intraocular pressure by soluble and membrane guanylate cyclases and their role in glaucoma - Buys, Emmanuel S.; Potter, Lincoln R.; Pasquale, Louis R.; Ksander, Bruce R. (Frontiers in Molecular Neuroscience, 2014)
Glaucoma is a progressive optic neuropathy characterized by visual field defects that ultimately lead to irreversible blindness (1, 2). By the year 2020, an estimated 80 million people will have glaucoma, 11 million of which will be bilaterally blind. Primary open-angle glaucoma (POAG) is the most common type of glaucoma. Elevated intraocular pressure (IOP) is currently the only risk factor amenable to treatment. How IOP is regulated and can be modulated remains a topic of active investigation. Available therapies, mostly geared towards lowering IOP, offer incomplete protection, and POAG often goes undetected until irreparable damage has been done, highlighting the need for novel therapeutic approaches, drug targets, and biomarkers (3, 4). In this review, the role of soluble (nitric oxide (NO)-activated) and membrane-bound, natriuretic peptide (NP)-activated guanylate cyclases that generate the secondary signaling molecule cyclic guanosine monophosphate (cGMP) in the regulation of IOP and in the pathophysiology of POAG will be discussed.